Factors influencing COVID-19 vaccine hesitancy and acceptance among the Pakistani population. Issue 10 (3rd October 2021) - Chaudhary, Farooq Ahmad; Ahmad, Basaruddin; Khalid, Muhammad Danial; Fazal, Ayesha; Javaid, Muhammad Mohsin; Butt, Danial Qasim
ABSTRACT: This study examined the factors associated with acceptance of the COVID-19 vaccine compared to hesitance in the Pakistani population and specifically focusing on the perceived beliefs, knowledge, concerns, risk, and safety perception relating to the COVID-19 vaccine. A total of 423 subjects were recruited from the Pakistan Institute of Medical Sciences, Islamabad, Pakistan. A 27-item valid and reliable questionnaire was used to assess socio-demographic characteristics, acceptance, and hesitance toward COVID-19 vaccine, perceived beliefs, knowledge, perceived concerns, risk, and safety of COVID-19 vaccines and its source of information. Chi-square tests and logistic regression were used for analysis. About 53% of the participants were planning to get vaccinated and a significantly greater proportion of better educated, higher income, and healthier participants in the vaccine acceptance group ( p < .05). The odds of knowing the vaccine they should get, having the confidence in the vaccine to stop the pandemic, and understanding the way vaccines work, were greater in the vaccine acceptance group than the vaccine-hesitant group (OR: 5.4; 3.5, 2.1, 3.1, respectively). Most participants (52.3%) obtained the information regarding the COVID-19 vaccine from the print and live news media (52.3%) followed by social media (23.7%). The lack of knowledge, understanding, and perception of the risk, safety partly explains the low rate of vaccine acceptance in the Pakistani population. Strategies to raise awareness of the benefits of vaccination should target individuals in the lower socioeconomic group and those with chronic disease.